Private foreign investment in Bangladesh - Reza, Sadrel; Rashid, M. Ali; Alam, A.H.M.Mahbubul (Dhaka : University Press, 1987)
Business
Keywords: Foreign investment; Export processing zone; Local enterprises; Industrial policy